Effects of drawing and high-pressure sintering on the superconducting properties of (Ba, K)Fe2As2 powder-in-tube wires. (16th November 2015) - Pyon, Sunseng; Yamasaki, Yuji; Kajitani, Hideki; Koizumi, Norikiyo; Tsuchiya, Yuji; Awaji, Satoshi; Watanabe, Kazuo; Tamegai, Tsuyoshi
Abstract: The evolution of the superconducting properties of round wires of (Ba, K)Fe2 As2 fabricated by the powder-in-tube (PIT) method is systematically studied. After establishing the method to obtain the largest transport critical current density ( J c ) in round wires using the hot isostatic press technique, we investigated how the transition temperature ( T c ), J c, and microstructures change at each step of the wire fabrication. Unexpectedly, we find that superconducting properties of the wire core are significantly damaged by the drawing process. Systematic measurements of J c and T c of the core superconductor after each drawing and sintering process clarified the evolution of degradation by the drawing process and recovery by heat treatment.